AN ANALYSIS OF STUDENTS WRITING SKILLS OF NARRATIVE TEXT THROUGH PICTURE WORD INDUCTIVE MODELS AT GRADE XI IPA SMAN BINA BHAKTI SAPAT - Amri, Samsul; Anisa; Ardian, Edi (J-Shelves of Indragiri (JSI), 2023)
This research aimed to find out how to determine the skills of writing narrative texts through the inductive model of pictorial words in class XI of SMAN Bina Bhakti Sapat. The subjects of this study were 27 students of class XI IPA at SMAN Bina Bhakti Sapat in the academic year 2022–2023. In conducting this research, the type of research used was descriptive quantitative research. Quantitative data is taken from the written test. The results of the analysis show that there is an increase in students' ability to write narrative texts. The average test score of 70,59 demonstrates this. Regarding the students' test scores, the content aspect score was 21.29, the organization aspect was 15.22, the grammar aspect was 17.58, the mechanics aspect was 3.18, and the vocabulary aspect was 13.40. From the results of these data, it can be shown that the use of picture-word inductive models in writing narrative texts is effective. It can be concluded that students' ability to write narrative texts has increased by using picture-word inductive models. Writing narrative text has been improved by using the picture-word inductive models. Therefore, the students became more active and enthusiastic in learning English and were active in English discussions.